2022
DOI: 10.1186/s12877-022-03421-9
|View full text |Cite
|
Sign up to set email alerts
|

Association between multimorbidity trajectories and incident disability among mid to older age adults: China Health and Retirement Longitudinal Study

Abstract: Background Although multimorbidity is a risk factor for disability, the relationship between the accumulative patterns of multimorbidity and disability remains poorly understood. The objective of this study was to identify the latent groups of multimorbidity trajectories among mid to older age adults and to examine their associations with incident disability. Methods We included 5,548 participants aged ≥ 45 years who participated in the China Healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 44 publications
0
1
0
1
Order By: Relevance
“…In the older participants studied, there was a high prevalence of chronic NCD, particularly cardiometabolic diseases, consistent with reports in the literature. A Chinese cohort study involving 5,548 older adults found the most prevalent condition in the study was multimorbidity, affecting 70% of participants, particularly cardiometabolic and osteoarticular diseases 20 . Zhao et al 21 assessed 5,749 in a Chinese city and found that 68.3% had cardiometabolic diseases, predominantly arterial hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…In the older participants studied, there was a high prevalence of chronic NCD, particularly cardiometabolic diseases, consistent with reports in the literature. A Chinese cohort study involving 5,548 older adults found the most prevalent condition in the study was multimorbidity, affecting 70% of participants, particularly cardiometabolic and osteoarticular diseases 20 . Zhao et al 21 assessed 5,749 in a Chinese city and found that 68.3% had cardiometabolic diseases, predominantly arterial hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Nos idosos estudados verificou-se grande ocorrência de DCNT, principalmente as cardiometabólicas, semelhante ao observado na literatura. Uma coorte realizada na China com 5.548 idosos, demonstrou que a condição mais prevalente na população estudada foi a multimorbidade, que afetou 70%, principalmente as doenças cardiometabólicas e osteoarticulares 20 . Zhao et al 21 , avaliaram 5.749 idosos em uma cidade chinesa e constataram que 68,3% da amostra possuía doenças cardiometabólicas, com destaque a hipertensão arterial.…”
Section: Discussionunclassified